Comparative Study Between Tubularized Incised Plate Urethroplasty and Transverse Prepuceal Only Island Flap Urethroplasty for the Management of Distal Penile Hypospadias (Bangladesh Journal of Urology, 2020)
Introduction: The optimal treatment of hypospadias remains controversial. Severaltechniques have been described, but the best approach remains unsettled.Objective:To compare the outcomes of two popular methods, Tubularized incised plateurethroplasty (TIPU) and Transverse preputialonlay island flap (TPOIF) for the correctionof distal penile hypospadias.Materials and method: This prospective interventional study was conducted in theDepartment of Urology, Dhaka Medical College Hospital, during the period of September2015 to March 2017. 40 patients with distal hypospadias with minimum or no chordeeand no previous history of circumcision or hypospadias surgery were allocated into twogroups by simple random sampling with equal number of distribution. In Group-A, patientswere subjected to correct the defect by TIPU procedure while in Group-B, they wereoperated by TPOIF urethroplasty technique. In this study, the outcomes of theaforementioned procedures were compared in terms of operative time, surgicalcomplications and cosmetic outcome.Result: Mean age and meatal position of the patients in Group-A and Group-B werecomparable. The mean operation time of Group-B (100.78 ±16.66 min) was higher thanGroup-A (89.98 ±19.80 min). Complications in terms of UCF and meatal stenosis werehigher in Group-A than in Group-B, 26.31% vs. 16.67% and 36.84% vs. 5.56%respectively, but were lower for wound disruption, 0% vs. 11.11%. Although differencebetween the groups was not statistically significant in case of UCF and wound disruption(p value >0.05), it was significant in meatal stenosis (p value